Türkiye’nin Bosna-Hersek’e Yönelik Resmi Kalkınma Yardımlarının Sosyal Politika Açısından Analizi (4th International Balkan Studies Congress Proceedings, 2025)
Official development assistance (ODA) is a tool used by developed countries through their national agencies to establish cooperation with less developed or developing countries and contribute to the improvement of their welfare. This tool, which became widespread globally after World War II, is no longer used exclusively by developed countries today. It is observed that Türki-ye, especially after the 1990s, has been actively conducting official development activities in various regions of the world, primarily in Central Asia, the Balkans, and African countries, where it has historical ties. Official development assistan-ce can be used for a wide range of purposes, including meeting emergency ne-eds, providing humanitarian aid, fostering solidarity, preserving historical ties, and advancing national, commercial, political, and strategic interests. Türkiye, with its aid model referred to as the “Turkish Model of Development Assistance,” follows a solidarity-based strategy that prioritizes human well-being in line with the tradition of foundations, setting itself apart from traditional donors. With its official development assistance amount reaching 8 billion, Türkiye ranks first among countries in terms of the ratio of aid to gross national income. When exa-mining the nature of this aid, activities can be found in various sectors such as education, health, administrative and civil infrastructure, production, industry, and trade. These activities can be considered within the framework of social po-licy. In its broadest sense, social policy refers to policies aimed at all segments of society and addressing all social issues. The focus here is primarily on improving the welfare of those who are socio-economically disadvantaged and vulnerable. It is important to examine how much of the aid provided falls within the scope of social policy. This will facilitate assessing its contribution to the welfare of society and identifying any shortcomings. Based on this, the aim of this study is to analyze Türkiye’s official development assistance to Bosnia and Herzegovina, which is the leading 69 recipient of Turkish aid among the Balkan countries, from a social policy perspective. In the analysis, data presented in the Türkiye Development Assistance Reports prepared by TIKA were classified to interpret the nature and effectiveness of the aid. As a result, it was observed that the aid provided is concentrated in areas such as education and health, which are key concerns within the broad scope of social policy.